PENGARUH WORK LIFE BALANCE DAN LINGKUNGAN KERJA TERHADAP KEPUASAN KERJA MELALUI EMPLOYEE ENGAGEMENT DENGAN KESEHATAN MENTAL SEBAGAI VARIABEL MODERATOR PADA KARYAWAN GENERASI MILENIAL (STUDI KASUS: DIREKTORAT KEUANGAN PT ANGKASA PURA I (PERSERO)) - Kusumawardani Saptono, Niken; Supriyadi, Edy; Yusuf, Tabroni (EKOBISMAN : JURNAL EKONOMI BISNIS MANAJEMEN, 2020)
The purpose of this study was to determine the effect of work life balance, work environment, and employee engagement on job satisfaction and mental health as a moderator variable. The population of this research was the millennial generation of Finance directorate employees in PT Angkasa Pura I (Persero). The number of the respodent was 71 people. The statistical method used in this study is Structural Equation Modeling (SEM) which is operated through the WarpPLS program. In this study, the results show that the variables of the work environment have positive and significant influences on employee engagement, even work life balance has no influence on employee engagement. Variables of work life balance, work environment, and employee engagement have positive and significant influences on job satisfaction. Mental health as a moderator variable has positive and significant influences to encourage work environment on employee engagement, even has no influences to encourage work life balance on employee engagement.